а) 3х-3у+ах-ау= 3(х-у)+а(х-у)= (3+а)(х-у).
б) 15х+3у+5мх+му= 5х(3+м)+у(3+м)= (5х+у)(3+м).
в) х²-х+2х-2= х²+х-2=(х+2)(х-1).
г) х²+х-4х-4= х²+3х-4=(х+4)(х-1).
д) 4х²-х-4х+1= 4х²-5х+1.
D= 25-16=9=3²
x1=(5+3)÷8=1
x2=(5-3)÷8=2/8=¼
4x²-5x+1= 4(x-1)(x-¼)=(x-1)(4x-1).
а) 3х-3у+ах-ау= 3(х-у)+а(х-у)= (3+а)(х-у).
б) 15х+3у+5мх+му= 5х(3+м)+у(3+м)= (5х+у)(3+м).
в) х²-х+2х-2= х²+х-2=(х+2)(х-1).
г) х²+х-4х-4= х²+3х-4=(х+4)(х-1).
д) 4х²-х-4х+1= 4х²-5х+1.
D= 25-16=9=3²
x1=(5+3)÷8=1
x2=(5-3)÷8=2/8=¼
4x²-5x+1= 4(x-1)(x-¼)=(x-1)(4x-1).